Acute respiratory symptoms and its associated factors among mothers who have under five-years-old children in northwest, Ethiopia - Zewudu Andualem; Zelalem Nigussie Azene; Jember Azanaw; Asefa Adimasu Taddese; Henok Dagne (Komiyama Printing Co. Ltd, 2020)
Abstract Background Poor air quality of the household is likely to be the largest public health concern in resource-constrained countries. Exposure to household air pollution, poor working environment, and fuel type used at household level have been associated with respiratory symptoms. This study aimed to assess acute respiratory symptoms and its associated factors among mothers who have under five-years-old children in Gondar city, northwest Ethiopia. Method A cross-sectional study was carried out from February 15, 2019 to June 20, 2019. Study participants were selected using simple random sampling, and data were collected via face-to-face interviews. Binary logistic regression analysis was used to test the association of explanatory and outcome variables. Variables with p < 0.05 were considered as significantly associated with the outcome variable. Results The prevalence of respiratory symptoms among mothers of under-five years-old children in this study was 46.1%. Education (vocational training compared to cannot read and write) (adjusted odd ratio (AOR) = 0.26 at 95% confidence interval (CI): 0.08-0.82), working in dusty environment (AOR = 2.90 at 95% CI: 1.39-6.08), wood fire use (AOR = 0.37 at 95% CI: 0.16-0.85), living in mud- and wood-walled houses (AOR = 0.53 at CI: 0.32-0.89), recent house painting (AOR = 1.95 at 95% CI: 1.03-3.69), new carpet (AOR = 2.02 at 95% CI: 1.08-3.77), pesticide use (AOR = 1.71 at 95% CI: 1.03-2.84), damp stain (AOR = 2.45 at 95% CI: 1.04-5.75), spending longer time in house for 6 to 11 h (AOR = 2.59 at 95% CI: 1.53-4.37) and 11 to 15 h (AOR = 3.47 at 95% CI: 1.87-6.43), and living less than 100 m from unpaved roads/streets (AOR = 4.35 at 95% CI: 2.64-7.18) were significantly associated with respiratory symptoms among mothers of under-five years-old children. Conclusion Respiratory symptoms were common among mothers who have under five-years-old children. Air quality improvement, fuel selection, and residential planning will help to reduce respiratory symptoms.